A guide to information and policy analysis for agricultural decision making in Latin America and The Caribbean - Agricultural Planning and Policy Analysis Project in Latin America and the Caribbean (PROPLAN) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
280 páginas.